A study on factors influencing potential consumers purchase decision of automobile in Malaysia / Muhammad Arif Azim Mazridzuan - Mazridzuan, Muhammad Arif Azim (Faculty of Business and Management, 2018)
This thesis report the findings of a study issues concerning the factors influencing potential consumers purchase decision of automobile in Malaysia. There are too many car manufacturer and they compete with each other to improve their products. This study investigated the factors influencing purchase decision of automobile in Malaysia and research framework adapted from (Rajput, 2011), (Brown & Carpenter, 2000), (Austin and Dinan, 2005), (Glowa, 2001). This study was developed to investigate the factors influencing purchase decision of automobile in Malaysia. Price, ergonomic features and fuel efficiency are the factors that used to influence potential consumers purchase decision of automobile in Malaysia. Survey was conducted to gather the data and 130 respondents has been answered the questionnaire using online survey. Data analysis was then based on the 130 valid responses. Results show that ergonomic features and fuel efficiency significantly influence the purchase decision while there is no significant relationship with price. The findings would be useful to help manufactures or car makers to improve and upgrade their products.